ANALISIS YURIDIS UNDANG-UNDANG NOMOR 28 TAHUN 2004 TENTANG YAYASAN TERHADAP FUNGSI SOSIAL YAYASAN: Indonesia - sinaga, Maruntung; Bhakti, Rizki Tri Anugrah (LPPM Universitas Putera Batam, 2020)
Foundations have fubctions and objectifes in the social field, one of the main focuses is education. Founded foundations that have full roles and responsibilities in managing them must fulfill the requirements in law number 28 of 2004 concerning Foundations. The purpose of thus study is to describe and analyze and find out (1) the social funtion of establishing a Foundation in accodance with law no. 28/2004 on Foundations, (2) the forms of foundation activities that are permitted in the law of profit. Some problems with the establishment of educational foundations with the emergence of social functions of foundations as well as forms of activities that are not synchronous. The main source of this research is available data in the form of books and journals as well as written approach used is nornative juridical by examining and interpreting theoretical matters regarding doctrine, and social-related legal norms. Data analysis with qualitative analysis. Based on the results of research and deductive conclusions can be drawn by way of thinking based on general facts and then conclusions drawn specifically